Smart city re-imagined: City planning and GeoAI in the age of big data - Reza Mortaheb; Piotr Jankowski (Journal of Urban Management, 2023)
This paper aims to engage with the ongoing debates on the role of planning in future smart cities, to make a case for a reconceptualization of the technocentric notion of the smart city, and to elevate the position of city planning within the smart-city discourse. The central argument made is that the smart city could exploit the synergies between city planning and three techno-scientific domains including Big Data, Geographic Information Science and Systems, and Data Science-which collectively constitute an emerging field known as Geospatial Artificial Intelligence (GeoAI)- to meet four overarching policy goals: 1) to enhance the efficiency of urban services and functions; 2) to improve quality of life for all urban citizens; 3) to address the pressing societal, ecological and economic challenges that could plague urban systems on different levels; and, 4) to contribute to the production of spatial data, information and knowledge on human-urban dynamics. In addition, the paper defines a human-centered conceptual framework illustrating how the cross-pollination between city planning and the three techno-scientific fields could enhance the planning practice and accomplish the smart-city policy goals. The methodology employed in this study entails a systematic review of the literature. In addition to discussing the latest achievements as well as the progress made on the nexus of city planning and GeoAI, the paper also highlights the barriers to the application of GeoAI in the planning, design and management of smart cities and identifies potential avenues for future research.
Keywords: 710; AI in urban planning; Geographic information science and systems; Smart city; Sustainable urban development; Urban digital twins